A speed sensorless field oriented control of parallel- connected dual PMSM - Asri, A.; Ishak, D.; Iqbal, S.; Kamarol, M. (2011 IEEE International Conference on Control System, Computing and Engineering, 2011)
This paper presents a speed sensorless field oriented control of parallel-connected dual permanent magnet synchronous motors (PMSM) fed by a single inverter. The speed of the both motors is controlled by using FOC method and averaging technique. In this project, model reference adaptive system (MRAS) method has been applied to the system in order to eliminate the use of speed sensor. The simulation work is implemented in Matlab/Simulink software in order to verify the proposed control strategy. The effectiveness of this proposed control strategy was confirmed during motor operations with balanced and unbalanced load levels at different speed range.